Implementation of Application of Mortgage Rights Electronically - Ahmed Alfatino; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to find out and analyze the implementation of mortgage rights electronically in the conception of legal certainty. To find out and analyze the effectiveness of the implementation of mortgage rights electronically. The method used by the researcher is Juridical Empirical (sociolegal research) and the specifications in this study are descriptive analytical. Based on the results of the study that Implementation of Electronic Mortgage Implementation in the Conception of Legal Certainty is that the Granting of Mortgage shall be registered at the Land Office no later than 7 (seven) working days after the signing of the Deed of Granting of Mortgage. The obligation of PPAT to register the Deed of Granting Mortgage at the latest 7 days after being signed as mentioned above has not been running properly. In its implementation, it is still experiencing difficulties caused by the lack of socialization to Registrants regarding the application of the electronic system. The Effectiveness of the Implementation of Mortgages Electronically is that with the electronic-based policy, it is very effective and efficient for all related parties, namely the Community, PPAT, Banks, and the Government in the Mortgage Registration process.